The altar call its origins and present usage - Bennett, David (Brisbane, QLD Camp Hill, 2000)
Includes bibliographical references and index.
A revision of author's thesis (M.Th, Australian College of Theology, Sydney ; 1997) entitled " The public invitation system in evangelism"
Keywords: Preaching -- the altar call